2016
DOI: 10.1002/ejp.931
|View full text |Cite
|
Sign up to set email alerts
|

Clinical practice guidelines for the noninvasive management of low back pain: A systematic review by the Ontario Protocol for Traffic Injury Management (OPTIMa) Collaboration

Abstract: We conducted a systematic review of guidelines on the management of low back pain (LBP) to assess their methodological quality and guide care. We synthesized guidelines on the management of LBP published from 2005 to 2014 following best evidence synthesis principles. We searched MEDLINE, EMBASE, CINAHL, PsycINFO, Cochrane, DARE, National Health Services Economic Evaluation Database, Health Technology Assessment Database, Index to Chiropractic Literature and grey literature. Independent reviewers critically app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
253
0
40

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(300 citation statements)
references
References 46 publications
(134 reference statements)
7
253
0
40
Order By: Relevance
“…Relative indications for acute surgery are discussed in the next section. Nonoperative management should consist of a multimodal approach including anti-inflammatory medications, education, and physical therapy [48].…”
Section: Treatment Non-operativementioning
confidence: 99%
“…Relative indications for acute surgery are discussed in the next section. Nonoperative management should consist of a multimodal approach including anti-inflammatory medications, education, and physical therapy [48].…”
Section: Treatment Non-operativementioning
confidence: 99%
“…However, several recent reviews on low back pain have only found good evidence for NSAIDs for acute, subacute and nonradicular low back pain [7][8]. Thus, it appears that the standard medical therapy recommended in this review is incongruent with the literature and multi-disciplinary best practice guidelines.…”
mentioning
confidence: 79%
“…For this study, the research team reviewed the literature and selected a well-constructed recent systematic review of LBP clinical practice guidelines4 , 16 supplemented by a comprehensive systematic review of non-invasive treatments for LBP 17. This high-quality evidence was identified to closely reflect optimal clinical practice.…”
Section: Methodsmentioning
confidence: 99%